P4-based implementation of BIER and BIER-FRR for scalable and resilient multicast. (1st November 2020) - Merling, Daniel; Lindner, Steffen; Menth, Michael
Abstract: Bit Indexed Explicit Replication (BIER) is a novel IP multicast (IPMC) forwarding paradigm proposed by the IETF. It offers a transport layer for other IPMC traffic, keeps core routers unaware of IPMC groups, and utilizes a routing underlay, e.g., an IP network, for its forwarding decisions. With BIER, core networks do not require dynamic signaling and support a large number of IPMC groups with large churn rates. The contribution of this work is threefold. First, we propose a novel fast reroute (FRR) mechanism for BIER (BIER-FRR) so that IPMC traffic can be rerouted as soon as the routing underlay is able to carry traffic again after a failure. In particular, BIER-FRR enables BIER to profit from FRR mechanisms in the routing underlay. Second, we describe a prototype for BIER and BIER-FRR within an IP network with IP fast reroute (IP-FRR). It is based on the programmable data plane technology P4. Third, we propose a controller hierarchy with local controllers for local tasks, in particular to enable IP-FRR and BIER-FRR. The prototype demonstrates that BIER-FRR reduces the protection time for BIER traffic to the protection time for unicast traffic in the routing underlay.